From “Aged Care” to “Aging Well”: An Integrative Framework for High-Quality Development in the Silver Economy—An Economic Analysis of Demand, Supply, and Institutional Interactions - Li, Jialu (Exploring Science Academic Conference Series, 2026)
The accelerating process of population aging in China and the rise of the “new elderly” group (those born after the 1960s and 1970s) are driving a profound transformation of the silver economy from “basic elderly care” to “high-quality enjoyment of old age”. However, existing studies often adopt a single perspective, lacking a systematic analysis of the interactive mechanisms among the demand side, supply side, and institutional side. This paper constructs an integrated analytical framework encompassing demand, supply, and institutional aspects, revealing the interactive mechanisms among these three dimensions and their impact pathways on the high-quality development of the silver economy. The research finds that demand drives supply via scale, structure, and price effects; supply feeds back to demand by creating scenarios, reducing costs, and enhancing experience; and institutions regulate supply-demand matching by correcting market failures, providing incentives, and standardizing order. Furthermore, this paper applies the proposed framework from a dynamic evolutionary perspective to outline the developmental pathways of the silver economy. This research provides an integrated theoretical tool for understanding the intrinsic logic of the silver economy and offers an analytical framework for precise policy formulation and strategic corporate planning.